Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Osteoporosis Assessment. (7th September 2021) - Dimar, John; Bisson, Erica F; Dhall, Sanjay; Harrop, James S; Hoh, Daniel J; Mohamed, Basma; Wang, Marjorie C; Mummaneni, Praveen V
Abstract: BACKGROUND: Osteoporosis is a metabolic bone disease that commonly affects the elderly. Degenerative spinal disease that may require surgical intervention is also prevalent in this susceptible population. If undiagnosed or untreated before spine surgery, osteoporosis may result in an increased risk of postoperative adverse events. Nontreatment of osteoporosis preoperatively may be related to a poor understanding of bone physiology, a lack of standardized treatment algorithms, limited cost-effective interventions, and reluctance by spine surgeons to be the primary provider of osteoporosis management. OBJECTIVE: The objective of this evidence-based review is to develop guidelines for the preoperative assessment and treatment of osteoporosis in patients undergoing spine surgery. METHODS: A systematic review of the literature was performed using the National Library of Medicine/PubMed database and Embase for studies relevant to preoperative diagnostic studies that predict increased risk of osteoporosis-related postoperative adverse events and whether the preoperative treatment of low bone mineral density (BMD) in patients with osteoporosis improves outcome. RESULTS: Out of 281 studies, 17 met the inclusion criteria and were included for systematic review. The task force affirmed a Grade B recommendation that preoperative osteoporosis testing with a dual-energy X-ray absorptiometry scan (T-score < −2.5), a computed tomography scan (Hounsfield units <97.9), and serum vitamin D3 level (<20 ng/mL) predict an increased risk of osteoporosis-related adverse events after spine surgery. The task force determined a Grade B recommendation that preoperative osteoporosis treatment with teriparatide increases BMD, induces earlier and more robust fusion, and may improve select patient outcomes. There is insufficient evidence regarding preoperative treatment with bisphosphonates alone and postoperative outcome. CONCLUSION: This evidence-based clinical guideline provides a recommendation that patients with suspected osteoporosis undergo preoperative assessment and be appropriately counseled about the risk of postoperative adverse events if osteoporosis is confirmed. In addition, preoperative optimization of BMD with select treatments improves certain patient outcomes. The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/3-preoperative-osteoporosis-assessment